2011
DOI: 10.1073/pnas.1101148108
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic B-cell clusters that infiltrate transplanted human kidneys are clonal

Abstract: B cells and their immunoglobulin products participate in allograft rejection of transplanted human kidneys in which an interesting feature is the presence of a germinal center like B-cell clusters in the allograft. We report here that the immunoglobulin repertoires of these infiltrating B cells are highly restricted and the B cells within a cluster are clonal. Antibody libraries made from the infiltrating B cells of individual patients unexpectedly revealed that each patient utilizes a particular set of domina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 51 publications
(53 reference statements)
2
45
1
Order By: Relevance
“…These reactions were first identified in patients with autoimmune diseases, including multiple sclerosis (15), Sjögren's syndrome (57), RA (54), and Hashimoto's thyroiditis (5), and they have recently been identified in allografts (13) and cancer (14). They have been associated with the production of autoantibodies (39), and therefore, we speculate that they are also present in chronic HCV infection.…”
Section: Discussionmentioning
confidence: 99%
“…These reactions were first identified in patients with autoimmune diseases, including multiple sclerosis (15), Sjögren's syndrome (57), RA (54), and Hashimoto's thyroiditis (5), and they have recently been identified in allografts (13) and cancer (14). They have been associated with the production of autoantibodies (39), and therefore, we speculate that they are also present in chronic HCV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, one group suggested a connection between the microbiome and chronic injury. 47 Finally, although its importance was recognized early, recent studies have re-emphasized the importance of nonadherence as either a causative or contributing factor for some cases of late failure.…”
Section: Contributing Factorsmentioning
confidence: 99%
“…While the mechanism of chronic kidney rejection is far from certain, recent studies have suggested that a large set of genes that encode proteins of the innate and adaptive immune system are expressed in the host during rejection (2). Another interesting immunological feature of transplanted kidneys is the appearance of highly organized ectopic B-cell clusters in the transplant (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14).…”
mentioning
confidence: 99%